2010
DOI: 10.1007/s00253-010-2892-9
|View full text |Cite
|
Sign up to set email alerts
|

Lectins: production and practical applications

Abstract: Lectins are proteins found in a diversity of organisms. They possess the ability to agglutinate erythrocytes with known carbohydrate specificity since they have at least one non-catalytic domain that binds reversibly to specific monosaccharides or oligosaccharides. This articles aims to review the production and practical applications of lectins. Lectins are isolated from their natural sources by chromatographic procedures or produced by recombinant DNA technology. The yields of animal lectins are usually low … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
161
0
8

Year Published

2012
2012
2022
2022

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 259 publications
(170 citation statements)
references
References 95 publications
1
161
0
8
Order By: Relevance
“…Similarly, cysteine proteases occur in latex of papaya (Carica papaya) and wild fig (Ficusvirgata) were found highly toxic to caterpillars of herbivorous insects [9]. Similarly, few natural products such as sugar mimic alkaloids [30,31] flavonoids [32,33], sesquiterpenes [34], triterpenes [35] and thiophenes [36], lectins [37,38], latex proteins [39], acetogenins [40] and other botanicals [8,41] isolated from different plants species were found active against silk worm, Bombyx mori and termites [42]. Similarly latex chitinases [43], glycosidase inhibitors [44] and few secondary metabolites of plant origin show strong insecticidal properties [10].…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, cysteine proteases occur in latex of papaya (Carica papaya) and wild fig (Ficusvirgata) were found highly toxic to caterpillars of herbivorous insects [9]. Similarly, few natural products such as sugar mimic alkaloids [30,31] flavonoids [32,33], sesquiterpenes [34], triterpenes [35] and thiophenes [36], lectins [37,38], latex proteins [39], acetogenins [40] and other botanicals [8,41] isolated from different plants species were found active against silk worm, Bombyx mori and termites [42]. Similarly latex chitinases [43], glycosidase inhibitors [44] and few secondary metabolites of plant origin show strong insecticidal properties [10].…”
Section: Discussionmentioning
confidence: 99%
“…2) Recently, a lectin microarray was developed as a high-throughput technology for glycan profiling of glycoproteins and cells, 3) and the importance of lectins in the fields is increasing. Since increase in the repertoire of lectins makes the technology more effective, screening and isolation of novel lectins with various carbohydrate-binding specificities are still needed.…”
mentioning
confidence: 99%
“…This suggested that bioactive compounds which inhibit the growth of bacteria were mostly semi-polar, and thus, could be easily extracted by methanol which was also semi polar. Antimicrobial compounds produced by sponge might play an effective role in improving the efficiency of getting food which was in the form of bacteria [9].…”
Section: Discussionmentioning
confidence: 99%